Paciente masculino de 72 años de edad con Fibrosis Hepática - Álvarez Meza, Carla Patricia (2020)
Hepatic fibrosis is a disease that occurs as a scar tissue without cells, this tissue agglomerates in the liver because of chronic liver diseases at the insistence of a virus. Fibrosis in general is concomitant to the inflammatory processes maintained and is the body that causes fibrosis, but is not associated with acute liver diseases. The clinical case to which the investigation refers, is presented in a 72-year-old male patient, of widowed marital status, from the city of Babahoyo in the province of Los Ríos, who was diagnosed after having performed a resonance magnetic, abdominal ultrasound, cholangioresonance, a liver fibrosis by liver biopsy (tru-cut puncture). The objective of this clinical case is to perform an assessment of the nutritional status of the patient, through a nutritional diagnosis and a nutritional nutritional plan, which meets the needs and basic pathology of the patient, for this the patient's biochemical data was reviewed evidencing that their total cholesterol level is 240mg / dl, HDL 48mg / dl, LDL 90g / dl, triglycerides 80mg / dl, leukocytes 45.4mg / dl, hemoglobin 14.8g / dl, total proteins 7.93g / dl , Albumina 3.95g / dl, Glucose 98g / dl, more anthropometry evaluation, Weight 51kg, Size 1,42cm. It was concluded that the nutritional status of the patient is normal 25.2kg / m2 according to WHO BMI for older adults In uncomplicated liver diseases according to ESPEN, it recommends a distribution of macronutrients Carbohydrates 45 to 65% of the daily caloric intake, Proteins 1.0 to 1.5 g / kg / d, Fat 25 to 30% of the daily caloric intake. Based on these recommendations, a dietary therapeutic treatment with nutritional recommendations aimed at delaying and / or improving the patient's pathological status and maintaining a good nutritional status that affects a good standard of living will be proposed.